The commitments of academic staff and career in Malaysian universities - Noordin, Fauziah; Jusoff, Kamaruzaman; Hamali, Jamil; Mior Harun, Mior Harris (Canadian Center of Science and Education, 2008)
This article reports the study on career commitment of the academic staff of a local public university in Malaysia. The findings indicate that the academic staff of this university has higher level of career identity, low level of career resilient, and slightly high level of career planning. In addition, the results indicate that the respondents’ organizational tenure and annual salary have significant impact on their career resilience commitment. Other demographic variables showed no significant differences on career identity, career resilience, and career planning of the respondents. Implications for management and recommendations for future studies are highlighted.